A New Echo Signal Processing Method for Blind Area Imaging of SAR. Issue 4 (February 2020) - Ma, Yanheng; Hou, Jianqiang; Li, Gen
Abstract: The navigation, positioning and imaging of blind area (unknown area) has always been one of the research focuses in the field of unmanned and intelligent development. It is known that the choice of the grid where the sub-images are computed is a key point of the fast factorized back projection (FFBP, can be adopted to obtain images with arbitrary trajectories) algorithm. The grid partition of blind area may result in the loss of information in the imaging area due to the unpredictability. The same loss also exists when the angle of existence deviates from the ideal imaging angle. In this paper, a new echo signal processing method for blind area imaging of synthetic aperture radar (SAR) is proposed. It is presented that a method of describing irregular echoes by using generalized array. The definition and operation principle of generalized array are introduced, as well as the relationship between the echo described by generalized array and traditional echo. Finally, the simulation results show that the proposed method is beneficial to imaging processing, and the method has great significance to range migration correction in frequency domain and imaging grid generation of BP algorithm.